London rain : a new mystery featuring Josephine Tey - Upson, Nicola (Upson, Nicola. Josephine Tey mystery., 2016)
"May, 1937, London: The country is still reeling from Edward VIII's shocking decision to abdicate the throne in order to marry the woman he loves, Wallis Simpson. As London prepares for the historic Coronation of his brother, George, bestselling writer Josephine Tey is in town to oversee a BBC radio production of her play, Queen of Scots. When one of the BBC's best-known broadcasters is murdered at the height of the Coronation celebrations, Josephine has a front row seat. Detective Chief Inspector Archie Penrose is called to investigate--and then another killing occurs. The victim? The leading actress in Josephine's play, who happened to be the broadcaster's mistress. Adultery, treachery, and pent-up jealousies clearly haunt the BBC, suggesting the motive lies close to home, but Josephine suspects that the killings are linked to a decade-old scandal. His hands tied by bureaucracy and his attention taken by another, seemingly unrelated death, Archie is unable to solve the case. It's up to Josephine to untangle a long-hidden web of love, deceit and betrayal. As her own relationship with Marta Fox reaches a turning point, she must confront the consequences of romance gone awry"--